Reflexiones en torno a la sistematización de la práctica pedagógica - Marta Eugenia Sánchez-González (Revista Electrónica Educare)
This article brings together a series of reflections and experiences that the author has constructed for several years around the sistematization of pedagogy practices. This is important for considering that improving pedagogy requires rebuilding the work that has been done in diverse contexts of teaching and learning. That sitematization operates by means of diverse types of notes according to Shagoury y Miller (1993). Because the facts included in those notes allow us to think about our actions. This process allows researchers to contribute new elements to daily activities, as well as to adapt them much better to the needs and interests of the students and their context.